Widespread Ignorance on how to Adjust the Miami-J® Spinal Collar When Eating and Drinking Leads to Increased Aspiration Risk in Older People - Hudson, Murray AJ; Ehsanullah, Jasmine; Oungpasuk, Kanapath; O’Regan, Alice; Macpherson, Nicola; O’Gilvie, Aisha; Morgan, Cerys; Peck, George; Koizia, Louis J; Fertleman, Michael B (Archives of Clinical and Medical Case Reports, 2022)
Wearing a spinal collar can cause dysphagia [1, 2]. The limited evidence on swallow function when wearing a spinal collar is exclusively in younger volunteers [3, 4]. The manufacturer of the Miami-J® collar, Ossur® trains users to remove the sternal pad when a patient is eating or drinking. An 83-year-old male demonstrated deterioration in swallow function on video fluoroscopy when wearing the Miami-J collar with sternal pad in situ in comparison to wearing the collar with sternal pad removed, highlighting the importance of its removal. We identified poor knowledge across the MDT about removing the pad during oral intake. This report seeks to alert all healthcare professionals of the importance of adjusting the sternal pad to avoid the significant risk of aspiration in the older person.